Functional Characterization of Undenatured Type II Collagen Supplements: Are They Interchangeable?. (2nd November 2022) - Harris, Robert B.; Fonseca, Fernando L. A; Sharp, Matthew H.; Ottinger, Charlie R.
Abstract: Undenatured (native) type II collagen is a dietary supplement ingredient reported to support joint health in healthy individuals by providing relief from symptoms of stiffness and discomfort and improving mobility. This benefit is thought to occur through oral tolerance, a mechanism whereby the immune system distinguishes between innocuous material in the gut and potentially harmful foreign invaders. The presence of antigenic epitopes in undenatured type II collagen, but not in denatured (hydrolyzed) collagen, is thought to be the basis for the therapeutic benefits. The purpose of this study was to investigate the physicochemical and analytical characteristics of type II collagen supplements currently available on the market and to explore whether they might be sufficiently similar in their physical properties to yield similar benefits in promoting joint health. Collagen type II supplement powders (raw material) and capsules (products in the market) were examined for color, particle size, quality profiles, fatty acid profiles, electron microscopy, and were analyzed for amino acid content as well as antigenic potential via an ELISA assay. Powders labeled as undenatured type II collagen were found to have markedly different properties, including the size of collagen fibers as per electron microscopy and antigenic configuration as per the ELISA assay. As significant differences were found between products, it allows consumers and practitioners to not assume that products labeled as undenatured (native) type II collagen are interchangeable.